Application of Arbitrary Vortex Method in Wind Tunnel Axial Fan Design. (October 2019) - Dachuan, Xu; Haifeng, Wang; Xiaoli, Qu; Yongsheng, Yu; Yu, Shi; Fang, Zhao
Abstract: The flow axial velocity is assumed equal everywhere in free vortex design method, and the pressure rise of flow pass through fan is assumed also equal at different radial height. But in arbitrary vortex design method, on the assumption that axial velocity along radial is variable, the flow rotational velocity along radial is not must an inverse distribution. Therefore, arbitrary vortex design method could have a more uniform axial velocity at the outlet of fan system by regulating the rotational velocity distribution. In the numerical simulation, the fan of a pilot wind tunnel is used as physical model. By comparison with the experimental data the reliability of the numerical simulation could be verified. Two fan physical models are established which are based on the designs of arbitrary vortex method and free vortex method. The result of numerical simulation indicated that compared to the free vortex method, the arbitrary vortex fan minished the separation on the tip and root of blade, obtained a more well uniform axial velocity distribution at the outlet of fan system. And the efficiency of blade is also increased by arbitrary vortex method.